The marriage narrative - Kann, Claire (Berkley Romance, 2025)
"A love just for show grows into something more in this swoonworthy romance from the author of The Romantic Agenda. Zinnia is an ambitious, successful businesswoman who is not about to wait around for her One True Love. She turns her dating profile into a marriage-merger proposal: a few strategic meetings, move in together, get married-all within thirty days. Her friends think it will never work... until she meets Jordan, a near-perfect applicant with a big secret. Jordan's family has spent the last decade starring in a massively popular reality show about their lives. He has finally agreed to join the cast, but production wants him to marry an actress (his ex) in a romantic storyline to boost viewership. Convinced Zinnia is perfect for the role instead, Jordan proposes a mutually beneficial marriage agreement: she gets her business partner husband, and he gets to help his family on his terms. Together they face strict schedules, wild plot twists, and behind-the-scenes hostilities, all while acting like besotted newlyweds-an intense performance that evolves into a relationship they never expected. As the line between reality and show blurs, Zinnia and Jordan must choose between a clean contract or a beautifully messy love story"--